Economic surveys in under-developed countries : a study in methodology - Mukherjee, Prafulla Kumar (London : Asia Pub. House, 1960)
This book provides a new approach to research methodology in agricultural economics that has pertinent application in other underdeveloped countries than India. Seven of the eleven chapters are devoted to a scholarly and penetrating analysis of the relevance of the basic economic concepts of our Western culture in light of the peculiar characteristics of the underdeveloped rural economy of India.
Includes index.
Includes bibliographical references: p. 249-257.
lje 02/10/2018
Loans
Keywords: Economic surveys; Rural conditions; Developing countries